WORK ETHIC AND PRODUCTIVE BEHAVIOR OF FOOTWEAR CRAFTSMEN IN BOGOR DISTRICT - Anissa Lestari Kadiyono; Marina Sulastiana; Diana Harding; Arfian Arfian (Balai Besar Kerajinan dan Batik, 2021)
Footwear product is one of the superior products of Bogor Regency, which is distributed in 3 Subdistricts namely Ciomas Subdistrict, Tamansari Subdistrict, and Dramaga Subdistrict, and this sector has the potential to absorb labor, so as to reduce unemployment and affect the community economy. This needs special attention from the central government and regional governments to improve the footwear craftsman business. Factors that encourage increased productive behavior include the Work Ethic. The purpose of this study was to determine the effect of Work Ethic on Productive Behavior in Footwear Craftsmen in Bogor Regency. The sample of this study was 316 footwear craftsmen taken in 3 species. Quantitative research methods with data analysis techniques using LISREL SEM to test the hypothesis. The results showed that the Work Ethic affected the Productive Behavior of footwear craftsmen in Bogor Regency.